2005
DOI: 10.2174/1573395054065115
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12: An Update on its Immunological Activities, Signaling and Regulation of Gene Expression

Abstract: Interleukin-12 (IL-12) is a heterodimeric cytokine composed of the p35 and p40 subunits. It is produced by antigen-presenting cells and plays a critical role in host defense against intracellular microbial infection and control of malignancy via its ability to stimulate both innate and adaptive immune effector cells. The potency of IL-12 renders itself to stringent regulation of the timing, locality and magnitude of its production during an immune response. Subversion of the delicate control and balance freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 221 publications
(238 reference statements)
3
90
1
4
Order By: Relevance
“…Higher SOCS3 expression or the IL-10/ID3 signaling loop may interfere with IL-12 expression. Indeed, Wnt5a-DCs failed to properly increase IRF1 and IRF8 transcription after stimulation, two positive and essential factors for priming IL-12 secretion (28).…”
Section: Discussionmentioning
confidence: 99%
“…Higher SOCS3 expression or the IL-10/ID3 signaling loop may interfere with IL-12 expression. Indeed, Wnt5a-DCs failed to properly increase IRF1 and IRF8 transcription after stimulation, two positive and essential factors for priming IL-12 secretion (28).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the difference between our study and that of Lucas et al (68) may be attributable to cross-talk between ERK1/2-mediated signaling and the PI3K-AKT pathway because only the latter was inhibited in our study. The regulation of IL-12 mRNA expression has been described extensively in a recent review (69) and is dependent upon the coordinated expression of IL-12 IL-12b and IL-12a genes, which are encoded on different chromosomes. Many studies have confirmed that the primary regulatory step for the expression of both IL-12 IL-12b and IL-12a genes is at the level of transcription: multiple transcription factors are known to be involved in regulation of these genes, e.g., NF-B (47), C/EBP␤ (41), PU.1 (70), IRF-1 (37, 71), IRF-2 (37), IRF-8/ICSBP (50,51), NFAT (72), AP-1 (73), and activator and repressor factors such as Kruppellike factor (74).…”
Section: Discussionmentioning
confidence: 99%
“…One of such SIMs which is a classical signal 3 cytokine with receptors expressed on T cells to enable them respond to shifts in their concentrations in the blood is IL-12. This cytokine, which has monocytes/macrophages, B cells, and dendritic cells as its established sources [35,36], is also critical for skewing CD4 T cell responses towards a T helper 1 (i.e., IFNγ hi , IL-4 low ) cytokine profile [37]. IL-12 secretion, together with many other SIMs, is known to be triggered and sustained during the immune activation that ensues in both the periphery and hepatic tissues during CHC.…”
Section: Discussionmentioning
confidence: 99%